Informasi Akuntansi dan Non Akuntansi Terhadap Initial Return Saham - Linggar Prawesti; Arum Indrasari (Journal of Accounting and Investment, 2014)
This research analyze and provide empirical evidence about the effect of accounting information (firm size, earning per share (EPS), financial leverage, return on asset (ROA)) and non accounting information (percentage of share ownership, auditor reputation, underwriter reputation, type of industry) to the initial returns at the initial public offering (IPO). This research use secondary data derived from the annual report where companies conduct the initial public offering (IPO) in the year of 2008-2012. The sample is 65 companies which is obtained by purposive sampling method. The analytical method used is multiple linear regressions with significance level 5%. Results of the research indicated that financial leverage have a negative and significant effect on the initial returns. Meanwhile variable firm size, earnings per share (EPS), return on assets (ROA), percentage of share ownership, auditor reputation, underwriter reputation, and the type of industry does not significantly effect the initial returns.